Climatic and structural controls on Late‐glacial and Holocene rockfall occurrence in high‐elevated rock walls of the Mont Blanc massif (Western Alps). Issue 13 (12th August 2020) - Gallach, Xavi; Carcaillet, Julien; Ravanel, Ludovic; Deline, Philip; Ogier, Christophe; Rossi, Magali; Malet, Emmanuel; Garcia‐Sellés, David
Abstract: In the Mont Blanc massif (European Western Alps), rockfalls are one of the main natural hazards for alpinists and infrastructure. Rockfall activity after the Little Ice Age is well documented. An increase in frequency during the last three decades is related to permafrost degradation caused by rising air temperatures. In order to understand whether climate exerts a long‐term control on rockfall occurrence, a selection of paleo‐rockfall scars was dated in the Glacier du Géant basin [>3200 m above sea level (a.s.l.)] using terrestrial cosmogenic nuclides. Rockfall occurrence was compared to different climatic and glacial proxies. This study presents 55 new samples (including replicates) and 25 previously‐published ages from nine sampling sites. In total, 62 dated rockfall events display ages ranging from 0.03 ± 0.02 ka to 88.40 ± 7.60 ka. Holocene ages and their uncertainties were used to perform a Kernel density function into a continuous dataset displaying rockfall probability per 100 years. Results highlight four Holocene periods of enhanced rockfall occurrence: (i) c . 7–5.7 ka, related to the Holocene Warm Periods; (ii) c . 4.5–4 ka, related to the Sub‐boreal Warm Period; (iii) c . 2.3–1.6 ka, related to the Roman Warm Period; and (iv) c . 0.9–0.3 ka, related to the Medieval Warm Period and beginning of the Little Ice Age. Laser and photogrammetric three‐dimensional (3D) models of the rock walls were produced to reconstruct the detached volumes from the best‐preserved rockfall scars (≤0.91 ± 0.12 ka). A structural study was carried out at the scale of the Glacier du Géant basin using aerial photographs, and at the scale of four selected rock walls using the 3D models. Two main vertical and one horizontal fracture sets were identified. They correspond respectively to alpine shear zones and veins opened‐up during long‐term exhumation of the Mont Blanc massif. Our study confirms that climate primarily controls rockfall occurrence, and that structural settings, coincident at both the massif and the rock wall scales, control the rock‐wall shapes as well as the geometry and volume of the rockfall events. © 2020 John Wiley & Sons, Ltd. Abstract : In the Mont Blanc massif rockfall occurrence is rising in correspondence with rising global air temperature. We date paleo‐rockfalls using terrestrial cosmogenic nuclide dating to study this relationship at a Holocene scale. Four periods of rockfall occurrence have been detected, related to warm climate periods.